Effect of soft skills on strategic alignment Applied research in Trade Bank of Iraq (TBI) - Taher Shnaiter, Abdulrahman; Mohammed Elewie, Elham; Raad Ibrahim, Ibtisamah (Opción, 2019)
The aim of the research is to identify the effect of soft skills in achieving strategic alignment in the Trade Bank of Iraqi. To achieve the aim of the research, the researcher designed a questionnaire that included (60) items to analysis of data from the research sample consisting of (45) respondents. Statistical program SPSS Many statistical methods were used to achieve the objective of the research. After conducting the analysis of the research data, the research reached a number of conclusions, the most important of which is a positive and significant effect of the soft skills and their distance in achieving strategic alignment. To develop strategies that contribute to the employment of soft skills and to acceptable degrees in order to achieve strategic alignment. This is due to the very close nature of the variables. And the fact that the bank’s research sample enjoys a good reputation in the local community despite its recent establishment, which makes it a fertile environment to attract the best skilled workers and apply these skills to achieve strategic alignment in order to achieve its objectives in the long, medium and short term and maintain a sustainable competitive advantage.